2011
DOI: 10.1016/j.dsr2.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Primary production in the Sub-Antarctic and Polar Frontal Zones south of Tasmania, Australia; SAZ-Sense survey, 2007

Abstract: The Sub-Antarctic Zone (SAZ) in the Southern Ocean provides a significant sink for atmospheric CO 2 and quantification of this sink is therefore important in models of climate change. During the SAZ-Sense (Sub-Antarctic Sensitivity to Environmental Change) survey conducted during austral summer 2007, we examined CO 2 sequestration through measurement of gross primary production rates using 14 C. Sampling was conducted in the SAZ to the south-west and south-east of Tasmania, and in the Polar Frontal Zone (PFZ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 78 publications
(74 reference statements)
7
57
0
Order By: Relevance
“…At the PFZ site P2 a deep chlorophyll maximum occurred just below the euphotic depth but above the mixed layer (compare Table 1, Fig. 2 and Westwood et al, 2011) and was characterised mainly of heavily silicified diatoms and nanoflagellates (de Salas et al, 2011). Bacterial and viral abundances were higher in the SAZ than the PFZ and highest at P3 (Evans et al, 2011).…”
Section: Study Areamentioning
confidence: 94%
See 1 more Smart Citation
“…At the PFZ site P2 a deep chlorophyll maximum occurred just below the euphotic depth but above the mixed layer (compare Table 1, Fig. 2 and Westwood et al, 2011) and was characterised mainly of heavily silicified diatoms and nanoflagellates (de Salas et al, 2011). Bacterial and viral abundances were higher in the SAZ than the PFZ and highest at P3 (Evans et al, 2011).…”
Section: Study Areamentioning
confidence: 94%
“…Primary production estimated from tracer incubation experiments exhibited strong variability at site P1 and similar values to P3, with somewhat lower values at the PFZ Table 1 Water column properties at the process stations. Westwood et al (2011). 3.…”
Section: Study Areamentioning
confidence: 99%
“…In the PFZ, non-limiting silicate concentrations occurred just below the euphotic depth (65 to 85 m), with a deep chlorophyll maximum (DCM) occurring just above the euphotic depth but below the mixed layer (Westwood et al, 2011). Unpublished data (B. Griffiths and B. Tilbrook, 2010) showed that silicate in surface waters was >10 µM during spring, but had been drawn down to limiting concentrations by the time of sampling in summer.…”
Section: Description Of the Region Under Studymentioning
confidence: 99%
“…See Westwood et al (2011) for a more detailed description of the GPP measurements performed during SAZ Sense. Six depths were sampled per CTD station ranging from the surface to 125 m. Sub-samples for each depth were then incubated with NaH 14 CO 3 for 1 h at 21 light intensities ranging from 0 to 416 µmol m −2 s −1 (CT Blue filter centered on 435 nm) in a temperature-controlled unit.…”
Section: Ancillary Measurementsmentioning
confidence: 99%
“…where J max is the maximum phytoplankton growth at a given T , assuming no light or nutrient limitation; J (z, t, T ) is the impact of light on growth rate, and is based on Westwood et al (2011), PAR is the photosynthetically available radiation, I (0, t) is the time-varying incident solar radiation at the surface, and Frac(z) is the light attenuation that is obtained from a single exponential decay law, with penetration depths based on SeaWiFS Kd-490 (which was the same as the value used by the Chen et al (1994) mixing scheme). Equation (B2) describes the zooplankton, represented as the balance between growth due to phytoplankton grazing (G(P, Z)) and losses due to zooplankton excretions (γ 2 Z) and mortality (µ Z Z 2 ).…”
Section: Appendix B Wombatmentioning
confidence: 99%